THE ROLE OF SOCIAL WORKERS IN PREPARING CHILDREN'S INDEPENDENCE AFTER SERVICE IN AN ORPHANAGE TO PREVENT THE RISK OF RE-NEGARDENMENT: PERAN PEKERJA SOSIAL DALAM MEMPERSIAPKAN KEMANDIRIAN ANAK PASCA PELAYANAN DI PANTI ASUHAN UNTUK MENCEGAH RISIKO KETERLANTARAN KEMBALI - Azzahra, Shafa Latifah; Hakim, Fatwa Nurul; Yusuf, Husmiati (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2025)
Children living within institutional care systems often face various challenges, not only in adapting to the environment of the orphanage but also in preparing for independence after leaving care. In this context, social workers act as frontliners who assist children in exploring their potential and providing services according to their needs. This study aims to explain the role of social workers in preparing social welfare residents for independent living after leaving institution through the implementation of vocational skills clasess at PSBR Taruna Jaya 1. This research employs a qualitative approach with data collected through interviews with social workers, child mentors, and foster child, as well as observations of skill development activities conducted at PSBR Taruna Jaya 1. The findings show that social workers play an active role in fostering the independence of neglected children through various roles, including enabler, broker, educator, empowerer, facilitator, and motivator. These roles contribute to building children’s independence through vocational training programs and social guidance. This study recommends strengthening the engagement and active involvement of social workers with social welfare residents, both during the guidance process and after termination.